2001
DOI: 10.1128/jvi.75.4.1672-1680.2001
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Functional Diversity of Human Immunodeficiency Virus Type 1 Subtype B Nef Primary Isolates

Abstract: We have characterized the functional integrity of seven primary Nef isolates: five from a long-term nonprogressing human immunodeficiency virus (HIV)-infected individual and one each from two patients with AIDS. One of the seven Nefs was defective for CD4 downregulation, two others were defective for PAK-2 activation, and one Nef was defective for PAK-2 activation and major histocompatibility complex (MHC) class I downregulation. Five of the Nefs were tested and found to be functional for the enhancement of vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
63
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 34 publications
(69 citation statements)
references
References 66 publications
6
63
0
Order By: Relevance
“…S1, top, in the supplemental material). Mutations of the SH3 binding domain (13,22,53) or the dimerization domain have consistently resulted in Nefs defective for multiple activities (5,12,17,26,35,37,(51)(52)(53). Specifically, mutations of the SH3 domain and dimerization domain result in Nefs defective for MHC class I downregulation, PAK-2 activation, and enhancement of virus particle infectivity, with the dimerization domain also defective in CD4 downregulation (5,35).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…S1, top, in the supplemental material). Mutations of the SH3 binding domain (13,22,53) or the dimerization domain have consistently resulted in Nefs defective for multiple activities (5,12,17,26,35,37,(51)(52)(53). Specifically, mutations of the SH3 domain and dimerization domain result in Nefs defective for MHC class I downregulation, PAK-2 activation, and enhancement of virus particle infectivity, with the dimerization domain also defective in CD4 downregulation (5,35).…”
mentioning
confidence: 99%
“…To this end, in a previous report we characterized seven primary isolate Nefs for each of the four genetically separable functions listed above (17). In this way we hoped to utilize the structural integrity of functioning Nefs to discover mechanistically interpretable structure-function relationships.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously demonstrated that a conserved phenylalanine in the C-terminal region of Nef (position 195 of SF2 Nef) is essential for PAK2 activation but not for CD4 downregulation, MHC class I downregulation, or the enhancement of viral infectivity (9). When the SF2 Nef F195 was mutated to isoleucine or arginine, the mutant lost its ability to activate PAK2 but retained the activities of CD4 or MHC class I downregulation and enhancement of infectivity (9) (data not shown).…”
mentioning
confidence: 99%